O Império e a Constituição Colonial Portuguesa - Silva, António Duarte (Imprensa de História Contemporânea, 2019)
Only in the twentieth century did the (so-called) Portuguese colonial constitution, in the material and formal sense, emerge. Only then the Empire and the Portuguese colonial law, as an exercise of power, were politically theorized. This book addresses that colonial constitution, in force in the eight colonies that, in the Third Portuguese Empire, formed a unique and homogeneous totality. The main issues of the colonial constitution were two: the organization of the colonial power and the status of indigenous people. Regulating domination and submission, the majority of colonial (overseas) law had not the formal or rigidity of constitutional law, but was dispersed in the common legislation, mostly administrative. In the analysis of this colonial constitution, this book reveals four great periods that have succeeded since the First Republic to the Decolonization Act of 1974.